Minimum vereistes vir 'n Suid-Afrikaanse onderwysstelsel: 'n Nederlands-Belgiese perspektief1 - Steyn, H. J. (Koers, 1994)
A common element among the different educational interest groups in South Africa is the expectation that a new education system should be acceptable to the international community. This expectation could therefore serve as one of the determinants that might guide the development of an education system that could serve the educational needs of a majority of interest groups. This article is the result of qualitative research by means of which the opinions of Belgian and Dutch communities were identified. These opinions regarding the education system policy, education system administration, school system and supportive services of the South African education system, can also be viewed as an exponent of the opinion of the international community.